2003
DOI: 10.1002/cbic.200200551
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formation of Divalent Metal Ions with Uridine 5′‐O‐Thiomonophosphate or Methyl Thiophosphate: Comparison of Complex Stabilities with Those of the Parent Phosphate Ligands

Abstract: The stability constants of the 1:1 complexes formed in aqueous solution between Mg2+, Ca2+, Sr2+, Ba2+, Mn2+, Co2+, Ni2+, Zn2+, or Cd2+ (M2+) and methyl thiophosphate (MeOPS(2-)) or uridine 5'-O-thiomonophosphate (UMPS(2-)) (PS(2-)=MeOPS(2-) or UMPS(2-)) have been determined (potentiometric pH titrations; 25 degrees C; I = 0.1 M, NaNO(3)). Comparison of these results for M(PS) complexes with those known for the parent M(PO) phosphate species, where PO(2-)=CH(3)OPO(2-)(3) or UMP(2-) (uridine 5'-monophosphate), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…The most popular alteration probably is the substitution of one of the oxygens by a sulfur atom. Such derivatives are then commonly employed as probes in ribozymes [28,181] Figure 14; bottom, left) [182]. Into the latter study also methyl thiophosphate (MeOPS 2-) was included for reasons of comparison.…”
Section: Complexes Of Nucleoside 5'-o-thiomonophosphatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most popular alteration probably is the substitution of one of the oxygens by a sulfur atom. Such derivatives are then commonly employed as probes in ribozymes [28,181] Figure 14; bottom, left) [182]. Into the latter study also methyl thiophosphate (MeOPS 2-) was included for reasons of comparison.…”
Section: Complexes Of Nucleoside 5'-o-thiomonophosphatesmentioning
confidence: 99%
“…Thereby it was proven, in accord with the discussion in Section 6.2.2, that the uracil residue is not involved in metal ion binding in M(UMPS) complexes. It may be added that thiophosphates are considerably less basic than phosphates with pK a values of about 4.8 [182,183]. It was further concluded that one of the two negative charge units in a thiophosphate group is located on the sulfur atom whereas monoprotonation occurs at one of the two terminal oxygen atoms [183].…”
Section: Complexes Of Nucleoside 5'-o-thiomonophosphatesmentioning
confidence: 99%
“…This shows that the thiocytosine residue compared with the parent cytosine residue has a much higher affinity toward the two metal ions considered. In addition, the fact that the stability of the Cd 2+ complex is even more enhanced than that of the Zn 2+ complex is in accord with the larger thiophilicity of Cd 2+ compared with that of Zn 2+ [52,53], and thus this observation demonstrates further the importance of (C2)S for metal ion binding. The stability enhancements indicated can be quantified with Eq.…”
Section: Stability Constants Of M 2+ /C2s Complexesmentioning
confidence: 77%
“…Mg 2+ and Mn 2+ prefer the harder oxygen ligands, while Cd 2+ , Zn 2+ and Pb 2+ display a pronounced preference for the softer aromatic-nitrogen and especially sulfur sites [84][85][86]150,151]. Mutations that exchange oxygen for sulfur or nitrogen groups can significantly suppress Mg 2+ binding, but the adverse effects can often be rescued by Cd 2+ or Mn 2+ .…”
Section: Metal Ion Switch Experimentsmentioning
confidence: 99%